2015
DOI: 10.1186/s12877-015-0175-0
|View full text |Cite
|
Sign up to set email alerts
|

Street crossing behavior in younger and older pedestrians: an eye- and head-tracking study

Abstract: BackgroundCrossing a street can be a very difficult task for older pedestrians. With increased age and potential cognitive decline, older people take the decision to cross a street primarily based on vehicles’ distance, and not on their speed. Furthermore, older pedestrians tend to overestimate their own walking speed, and could not adapt it according to the traffic conditions. Pedestrians’ behavior is often tested using virtual reality. Virtual reality presents the advantage of being safe, cost-effective, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 32 publications
2
48
1
2
Order By: Relevance
“…Accordingly, Kaimila et al (52) in Japan, and Rolison et al (53) in the United Kingdom, reported that elderly pedestrians were more susceptible to road traffic accidents when compared to younger individuals. According to the studies by Zito et al (54) in Switzerland, Cicchino and McCartt (55) and Doroudgar et al (56) in the USA, the main cause seemed to be a consequence of the aging process, which leads to a decrease in balance, hearing, vision, reaction time, muscle mass and bone mass in older individuals.…”
Section: Age Group (Years) Psychoactive Substancesmentioning
confidence: 97%
“…Accordingly, Kaimila et al (52) in Japan, and Rolison et al (53) in the United Kingdom, reported that elderly pedestrians were more susceptible to road traffic accidents when compared to younger individuals. According to the studies by Zito et al (54) in Switzerland, Cicchino and McCartt (55) and Doroudgar et al (56) in the USA, the main cause seemed to be a consequence of the aging process, which leads to a decrease in balance, hearing, vision, reaction time, muscle mass and bone mass in older individuals.…”
Section: Age Group (Years) Psychoactive Substancesmentioning
confidence: 97%
“…For instance, some of the most commonly fixated obstacles when moving through an environment are people [59], who are generally fixated at a distance to determine their heading and avoid collisions [55,59]. Similarly, eye movements are made to gauge the distance of approaching objects [e.g., a car, 60]. Viewers also sample ground information in a goal-driven manner, directing fixations ahead to check for changing terrain, as well as to closer regions that will be stepped on, and surface transitions to avoid [e.g., a curb, 61].…”
Section: Goal 3: How Do I Get From a To B?mentioning
confidence: 99%
“…These values (Table 1) were used as a reference to define the vehicles' trajectories to be used in the simulator. Contrary to other studies that usually assume constant speed (e.g., [19,20,22,[26][27][28][29]), the three types of speed profiles recorded in the observational study were implemented in the simulator. Speeds above 30 km/h were not considered since the study intended to evaluate the pedestrians' crossing decision-making, considering the approach of a vehicle at short distances from the crosswalk.…”
Section: Virtual Environmentmentioning
confidence: 99%